STRENGTHENING KNOWLEDGE OF DEMOCRACY AND PARTICIPATORY DEMOCRACY FOR YOUTH - Charpasit, Naiyana; Inchai, Puangtong (Journal of Social Science and Cultural, 2023)
The objectives of this research were to study 1) to enhance and foster participatory civic knowledge and participatory citizenship among youth. and 2) to investigate the level of participatory civic knowledge and participatory citizenship. The study sample consisted of 330 Yamane’s formula was used as a quantitative research. The questionnaire was used as a research tool. The statistical used for data analysis included percentages, mean, standard deviation, t - test, F - test, analysis of percentiles, and T - score to establish normal criteria. The research results indicated that 324 students, accounting for 98.2%, The mean score for promoting democracy before attending the training was equal to 31.15, with a standard deviation of 10.555. After attending the training, there was an improvement in the scores for enhancing democratic citizenship compared to before. The post - training average score was 58.10, with a standard deviation of 6.216. The pre - training average score for enhancing democratic citizenship with active participation was 29.41, with a standard deviation of 10.549. After participating in the training, there was an improvement in the scores for enhancing participatory democratic citizenship compared to before. The post - training average score was 54.29, with a standard deviation of 5.020, it was found that the group had a development score of 69.38, indicating a high level of development. The score for change was 38.50, it was found that the development score was 69.91, also indicating a high level of development. The score for change was 38.28. This research enhances knowledge of democracy and participatory democracy among young people. create knowledge of correct democratic governance It is a way of learning to build a strong democratic society in Thailand in the future. To create youths who have accurate knowledge as a key force in strengthening Thai democracy.